Analysis of Emotional Mental Conditions in Adolescents - Aridhona, Julia; Yanti, Devi; Nadhilla, Nurasiah (Universitas Negeri Semarang, 2024)
Adolescence is an age full of emotional changes, where emotional changes in adolescence are a complex problem, emotions are still passionate, while self-control is not yet mature, teenagers begin to search for their identity, wanting to know themselves truly. This research aims to analyze mental conditions in teenagers using descriptive methods, with a sample of 189 teenagers at SMA Negeri 1 Darul Imarah. The instrument in this study used the SDQ questionnaire from Goodman. The results of this research are based on aspects of mental health, based on the aspect of emotional problems, the majority are in the normal category, namely 120 (63.49%). The second aspect of behavioral problems with the most in the normal category was 127 (67.19%). The third aspect is hyperactivity with the highest number in the normal category, namely 165 (87.3%). The fourth aspect of peers has the highest number in the borderline category, namely 83 (43.91%), this requires counseling for adolescents who experience characteristics characterized by tending to be alone, not having good friends, not liking to play with others, often being bullied by friends. The fifth most prosocial aspect is in the normal category, namely 165 (87.3%). This can be seen in the ability to consider other peoples feelings, be willing to share with others, like to help, often be kind to others. Mental health conditions greatly influence teenagers psychological balance in dealing with themselves and the environment.